(untitled) (Journal of Oriental Studies, 2019)
The article deals with the valuable heritage of the Turkic peoples, published in the Kazakh language in the framework of the project “Kazynaly Ontustik” (“Wealth of the southern region”), which is implemented in the course of the State program of the Republic of Kazakhstan “Cultural heritage”. The main goal of the project is to open the way for the research of the world scientific space of the published literary heritage. Key words: Turkic peoples, The legacy of the great steppe, Wealth of the southern region, Cultural heritage, multivolume, wealth of the southern region.